Toward systematic integration between self-determination theory and motivational interviewing as examples of top-down and bottom-up intervention development: autonomy or volition as a fundamental theoretical principle - Vansteenkiste Maarten; Williams Geoffrey C; Resnicow Ken (BMC, 2012)
Abstract Clinical interventions can be developed through two distinct pathways. In the first, which we call top-down, a well-articulated theory drives the development of the intervention, whereas in the case of a bottom-up approach, clinical experience, more so than a dedicated theoretical perspective, drives the intervention. Using this dialectic, this paper discusses Self-Determination Theory (SDT) <abbrgrp>12</abbrgrp> and Motivational Interviewing (MI) <abbrgrp>3</abbrgrp> as prototypical examples of a top-down and bottom-up approaches, respectively. We sketch the different starting points, foci and developmental processes of SDT and MI, but equally note the complementary character and the potential for systematic integration between both approaches. Nevertheless, for a deeper integration to take place, we contend that MI researchers might want to embrace autonomy as a fundamental basic process underlying therapeutic change and we discuss the advantages of doing so.